2014
DOI: 10.1016/j.redox.2014.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin may impair iron status when fed to mice for six months

Abstract: Curcumin has been shown to have many potentially health beneficial properties in vitro and in animal models with clinical studies on the toxicity of curcumin reporting no major side effects. However, curcumin may chelate dietary trace elements and could thus potentially exert adverse effects. Here, we investigated the effects of a 6 month dietary supplementation with 0.2% curcumin on iron, zinc, and copper status in C57BL/6J mice. Compared to non-supplemented control mice, we observed a significant reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
69
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 50 publications
(45 reference statements)
9
69
3
Order By: Relevance
“…In agreement with these results, other studies reported similar results concerning the administration of curcumin [8,9] and administration of EPO. [16] However, to our knowledge, no study reported the effect of combined administration of curcumin and EPO on serum ferritin.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In agreement with these results, other studies reported similar results concerning the administration of curcumin [8,9] and administration of EPO. [16] However, to our knowledge, no study reported the effect of combined administration of curcumin and EPO on serum ferritin.…”
Section: Discussionsupporting
confidence: 88%
“…[20,21] In contrast to the current finding of absence of a significant effect of curcumin treatment on serum hepcidin concentrations, Chin et al found that the expression of hepcidin was significantly reduced in the liver of curcumin-fed mice along with depleted iron stores in the liver and the spleen. [9] The difference in the current study may be attributed to the change of administration method of curcumin (I/P daily injection for 21 days in the current study versus oral administration for 6 months in the mentioned study). In addition, in the current study, rats were fed standard pellet animal diet, whereas in the mentioned study, mice were fed a Western-type diet (20% fat and 10% sugar), and a high-fat diet has been suggested to promote iron deficiency by reducing duodenal iron absorption and by inducing inflammation.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…According to studies, curcumin has been characterized as a safe herbal compound, in a way that large doses of curcumin administration did not have serious adverse effects [16,17,18,19]. To the best of our knowledge, there is only one published study that investigated the effects of curcumin on the protein profile and oxidative damage in β-thalassemia patients applying proteomic techniques [20].…”
Section: Introductionmentioning
confidence: 99%